Strategy to Increase Brand Awareness Through Public Relations Activities with PENCILS Analysis Method: (Case Study : EDVI Beauty Glow Skincare) - Leonard Adrie Manafe; Yovita Ardeana (LPPPIPublishing, 2022)
No less rife with the cosmetic products number outside, skin care products in Indonesia lately have many fans ranging from all ages women and men. This means that the awareness level of the Indonesian people towards skin care is starting to increase, due to healthy and beautiful skin could increase the wearer confidence. This is the EDVI Beauty Glow Skincare focal point with the main goal of improving Indonesian skin problems. In this case study, researchers analyze how the EDVI public relations strategy in building products brand awareness using the PENCILS analysis method (Publications, Events, News, Community Involvement, Inform or Image, Lobbying and Negotiation, and Social Responsibility). This study uses a qualitative descriptive method with a narrative approach. Data collection techniques by interviews means, observation, and documentation. Interviews were conducted with the main informants, namely the EDVI owner, the Public Relations Division Head and two customers. The results show that EDVI implements the strategy of the PENCILS analysis method and what media is used. Strategies in the product form and company publicity, implementing program events, creating news, building good relations with the community, brand image, lobbying and negotiating skills, and corporate social responsibility to the community are PENCILS strategy forms that have proven successful in EDVI's efforts to build brand awareness.